Performance Score as a Measure of Organizational Effectiveness (Pravaha, 2021)
Organizational effectiveness is primarily about assessing an organization's performance using several criteria. This study aims to determine Nepalese telecommunications companies' organizational effectiveness using a performance score based on the most crucial non-financial performance metrics (namely, context, focus, integration, and interactivity). The quantitative research strategy was utilized to extract the information from the designated working delegates of the Nepalese telecommunication industry. The study employed a probability sampling technique, and the quantitative data were obtained using an organized questionnaire survey to compute the performance scores of the sample organizations and the industry as a whole. The findings revealed that Nepal Telecom's score was 58.40 (systematic) and Ncell's score was 69.54 (transforming), averaging the industry score was 61.43. Such scores represent the extent to which the Nepalese telecommunication industry has applied non-financial performance measures to enhance organizational performance knowledge.